Influence of Different Surface Treatments on the Shear Bond Strength of Resin Cement to Base Metal Alloys - Raeisosadat, Farkhondeh; Ghoveizi, Rahab; Eskandarion, Solmaz; Beyabanaki, Elaheh; Tavakolizadeh, Sara (Journal of Lasers in Medical Sciences, 2020)
Introduction: This study aimed to investigate the effect of different surface treatments on the bond strength of resin cement to nickel-chrome (Ni-Cr) alloy. Methods: Forty disk-shaped specimens of Ni-Cr alloy were prepared and divided into 4 groups. In the first group, the specimens’ surface was sandblasted with 50 μ Al2O3 particles. In the second group, the specimens were prepared with the Er:YAG laser. In the third group, the specimens were prepared using the Er:YAG laser after sandblasting. In the fourth group, the specimens’ surface was covered with a thin layer of MKZ metal primer after sandblasting. Then the cylinders of composite resin were bonded to the treated metal surfaces using Panavia F2.0 resin cement. All of the samples were subjected to 2000 thermal cycles. The shear bond strength was tested using a universal testing machine at the crosshead speed of 0.5 mm/min. The failure mode was also observed by a stereomicroscope. Data were analyzed using the one-way ANOVA and the Tukey HSD test at a significance level of 0.05. Results: The shear bond strength from the highest to the lowest were as follows: the Er:YAG laser group, the sandblast and MKZ primer combination group, the sandblast group, and the sandblast and Er:YAG laser combination group. The mean differences of shear bond strength between the Er:YAG laser group and the sandblast group (P = 0.047) and also between the Er:YAG laser group and the sandblast and Er:YAG laser combination group (P = 0.015) were statistically significant. Conclusion: Among the different surface treatments employed in this study, Er:YAG laser treatment increased the shear bond strength between the metal alloy and the resin cement (Pavnavia F2).